Short-term effect of botulinum toxin a injection on spastic arm function in post-stroke patients – preliminary findings - Tywoniuk, Jarosław; Mikołajewska, Emilia (Journal of Education, Health and Sport, 2015)
Tywoniuk Jarosław, Mikołajewska Emilia. Short-term effect of botulinum toxin a injection on spastic arm function in post-stroke patients – preliminary findings. Journal of Education, Health and Sport. 2015;5(8):322-325. ISSN 2391-8306. DOI 10.5281/zenodo.28942 http://dx.doi.org/10.5281/zenodo.28942 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A318-321 https://pbn.nauka.gov.pl/works/611589 POL-index https://pbn.nauka.gov.pl/polindex/browse/article/article-33a2a1b9-aac1-44c3-9247-62eb6ef514c2 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.07.2015. Revised 21.08.2015. Accepted: 21.08.2015. Short-term effect of botulinum toxin a injection on spastic arm function in post-stroke patients – preliminary findings Jarosław Tywoniuk1, Emilia Mikołajewska1,2,3 1 Rehabilitation Clinic, The 10th Clinical Military Hospital with Policlinic, Bydgoszcz, Poland 2 Department of Physiotherapy, Ludwik Rydygier Collegium Medium in Bydgoszcz, Nicolaus Copernicus University in Toruń, Poland 3 Neurocognitive Laboratory, Interdisciplinary Center for Modern Technologies, Nicolaus Copernicus University in Toruń, Poland Corresponding author: Emilia Mikołajewska Rehabilitation Clinic Military Clinical Hospital No. 10 and Polyclinic Powstańców Warszawy 5 85-681 Bydgoszcz, Poland e-mail: e.mikolajewska@wp.pl, emiliam@cm.umk.pl www: http://emikolajewska.netstrefa.eu Keywords: neurorehabilitation; physiotherapy; stroke; neurological deficit; therapeutic game, BTX-A. Abstract BACKGROUND: Despite efforts of scientists and clinicians evidences for the effectiveness of post-stroke rehabilitation programmes following BTX-A injection still look weak and unclear. OBJECTIVE: To evaluate the therapeutic effect of botulinum toxin A (BTX-A) injection on spastic upper limbs muscles. CASE STUDIES PRESENTATION: Six ambulatory post-stroke patients were recruited in this study. All parameters was measured twice: before the injection and after 4±1 weeks of treatment. The participants received the same number of therapeutic sessions (ambulatory physiotherapy: 5 days a week). A significant decrease in the AS/MAS and MRC scores observed after treatment showed improvement. CONCLUSIONS: Treatment with BTX-A, initially expensive, may be regarded as effective due to low incidence of side effects, short period of hospitalization (if necessary), and reduction in the use of other drugs/therapies.